Well-connected domains : towards an entangled Ottoman history - Firges, Pascal; Graf, Tobias P.; Roth, Christian; Tulasoglu, Gulay (Ottoman Empire and its heritage., 2014)
In Well-Connected Domains, Pascal W. Firges, Tobias P. Graf, Christian Roth, and Gülay Tulasoğlu showcase recent scholarship on the deep entanglements between the Ottoman Empire and the world beyond its borders, offering novel interpretations and fresh impulses for future research.